Decision Support System for Determining Recipients of Subsidized Food Materials for Poor Families Using the AHP Method at the Melati II Village Office - Rudi Hartono (International Journal of Basic and Applied Science, 2019)
Food substance subsidize to represent one of most having an effect on matter for impecunious family, pursuant to perception result which have been conducted passing implementation and usage applying program Office of Countryside of Jasmine II which have address in Unnamed Rd, Bar Terap, Perbaungan, Regency of Serdang Bedagai, North Sumatra, inferential that in determining decision of acceptance of food substance subsidize is Office of Countryside of Jasmine II have to design the system of receiver of food substance subsidize for society of Chief of village Mango which indigent effectively and efficient, as well as have to apply the method of Analytical Hierarchy Process (AHP) at acceptance of food substance subsidize.Others need also system implementation of decision supporter by using method of Analytical Hierarchy Process (AHP) to determine the society which indigent in acceptance of food substance subsidize.